2017
DOI: 10.1177/0271121417735901
|View full text |Cite
|
Sign up to set email alerts
|

Early Numeracy Trajectories: Baseline Performance Levels and Growth Rates in Young Children by Disability Status

Abstract: In its final report, the National Mathematics Advisory Panel (2008) highlighted the considerable math reasoning and problem-solving abilities that are acquired prior to kindergarten and underscored the need to include a focus on these youngest students' skill development as a means of promoting overall mathematical competency. Research suggests that differences in mathematical skills emerge early, prior to formal schooling (e.g.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Students from lower socioeconomic backgrounds (Jordan & Levine, 2009), with or at risk for a mathematical learning disability (Gersten et al, 2009), and students with disabilities, including students with autism, are more likely to have difficulties developing early number sense (Oswold et al, 2016; Titeca, Roeyers, Josephy, Ceulemans, & Desoete, 2014). Furthermore, recent research has shown children with disabilities enter Kindergarten with less number sense skills than typically developing peers and demonstrate less growth than children without disabilities (Hojnoski, Caskie, & Young, 2018).…”
mentioning
confidence: 99%
“…Students from lower socioeconomic backgrounds (Jordan & Levine, 2009), with or at risk for a mathematical learning disability (Gersten et al, 2009), and students with disabilities, including students with autism, are more likely to have difficulties developing early number sense (Oswold et al, 2016; Titeca, Roeyers, Josephy, Ceulemans, & Desoete, 2014). Furthermore, recent research has shown children with disabilities enter Kindergarten with less number sense skills than typically developing peers and demonstrate less growth than children without disabilities (Hojnoski, Caskie, & Young, 2018).…”
mentioning
confidence: 99%
“…It is important to note that special education preschool program was not superior to the regular education program for children without disabilities. However, this finding is still in favor of the quality of special education preschool program as the earlier studies have found different developmental trajectories in math achievement between children with and without disabilities, with children without disabilities having higher gains over the course of six months (Hojnoski, Caskie, & Miller Young, 2018). Regular preschool programs, although somewhat inferior to the special education program for children with intellectual disability, have also resulted in large and significant improvements.…”
Section: Discussionmentioning
confidence: 86%
“…A number of recent studies examining the development of math performance in primary school suggest a cumulative growth pattern (Aunola et al, 2004;Bodovski and Farkas, 2007;Morgan et al, 2011;Geary et al, 2012;Missall et al, 2012;Salaschek et al, 2014;Hojnoski et al, 2018). For a detailed synthesis of early numeracy growth studies, see Salaschek et al (2014).…”
Section: Introductionmentioning
confidence: 99%